ANALYSIS OF OUTPATIENT LENGTH OF STAY TIME OF OBSTETRICS & GYNECOLOGY DEPARTMENT IN EDELWEISS HOSPITAL - Salma Nareswari, Nabila
As the competition in healthcare services and patients expectations for service quality arise, hospitals are paying more attention in improving their quality from both clinical and management perspective. Minimizing length of stay (LOS) time in the outpatient departments will improve operational performance and in turn, increase patient satisfaction. Hence, Edelweiss Hospital in Bandung has set a standard of a maximum 2-hour LOS for its outpatient services. The aim of this study is to analyze the current performance of OLOS time compared to the standard, analyze each subprocess of OLOS, and ultimately propose suggestions to reduce the OLOS duration at Obstetrics & Gynecology Department as one of the busiest polyclinics in Edelweiss Hospital. In this study, the existing OLOS database collected by the IT team from August 2020-May 2023 will be analyzed using Control Chart and Process Capability to assess OLOS the performance. The results indicate that the OLOS data is currently out of control and not meeting the required standards.